Sistem Pendukung Keputusan Pemilihan Laptop Berbasis Web dengan Metode Analytical Hierarchy Process - Teddy Hartanto; Maria Irmina Prasetiyowati (Ultimatics : Jurnal Teknik Informatika, 2012)
If we talk about notebooks, there are so many choice of brands with various specifications that is sold in markets. It makes consumers sometimes having difficulty to select a notebook based on required specifications. Based on those reasons, the authors decides to design a notebooks decision support system to help consumers making a choice on notebooks based on required specifications.The Method that the authors use for this notebooks decision support system is Analitical Hierarcy Process. This method chosen because it can choose the best alternative from some alternatives. The best alternative is best notebook based on specified criteria. The web based notebooks decision support system program designed based on Hyper Text Preprocessor (PHP) software dan MySQL for its database. The results of implementation from Analitical Hierarcy Process can be applied on the notebooks decision support system. Keywords: Decision Support System, Analitical Hierarcy Process, Notebooks Selection